The bicuspid aortic valve and related disorders - Yuan,Shi-Min (2010)
Bicuspid aortic valve (BAV) is the most common congenital cardiac malformation, affecting 1-2% of the population, with strong male predominance. Individuals may have a normally functioning BAV, and may be unaware of its presence and the potential risk of complications. However, they may easily develop aortic valve disorders: either stenotic or regurgitant, or both. Today, BAV is recognized as a syndrome incorporating aortic valve disorders and aortic wall abnormalities, including aortic dilation, dissection or rupture. Congenital or hereditary diseases such as ventricular septal defect, patent ductus arteriosus, coarctation of the aorta, Turner's syndrome, Marfan's syndrome etc., may frequently be associated with BAV. Infective endocarditis and occasionally thrombus formation may develop during the lives of BAV patients. Elevated cholesterol or C-reactive protein may be seen in laboratory findings of these patients. Beta-blockers and statins are the possibilities for medical treatment, and aortic valve repair/replacement and ascending aorta replacement are indicated for patients with a severely diseased aortic valve and aorta. Rigorous follow-up throughout life is mandatory after BAV has been diagnosed. The aim of the present article was to describe the implications of BAV and its associated disorders, and to discuss diagnostic and treatment strategies.